MATERIALISM AND COMMODIFICATION OF THE SACRED: A POLITICAL ECONOMY OF SPIRITUAL MATERIALISM IN NIGERIA - Al Chukwuma, Okoli; Ahar Clement, Uhembe (European Scientific Journal, ESJ, 2014)
This paper is an attempt to proffer a political economy reflection on the phenomenon of spiritual materialism in Nigeria. By way of qualitative analysis of relevant secondary sources, predicated on the Marxian Political Economy approach, the paper posits that spiritual materialism is a manifestation of the ‘queer capitalist tendency’ in the context of the contemporary global market economy order, characterized by excessive consumerism, commercialism, monetization, and marketisation of the wider society. The paper adds that the prevailing material and existential conditions arising from the Nigerian political economy tend to promote the consciousness and practice of spiritual materialism. The paper recommends that the activities of spiritual materialists in Nigeria should be harnessed and taxed by the government so as to raise revenue for the state.